Faltings extension and Hodge-Tate filtration for abelian varieties over p-adic local fields with imperfect residue fields - He, Tongmu (Canadian mathematical bulletin, 2021)
Let K be a complete discrete valuation field of characteristic $0$ , with not necessarily perfect residue field of characteristic $p>0$ . We define a Faltings extension of $\mathcal {O}_K$ over $\mathbb {Z}_p$ , and we construct a Hodge-Tate filtration for abelian varieties over K by generalizing Fontaine’s construction [Fon82] where he treated the perfect residue field case.